Innovative Approaches to the Administration of Social Support and Interagency Cooperation in the Field of Social Services - Cherneta, Svitlana; Bychuk, Iryna; Stepanenko, Viktoriia; Kolosok, Andrii; Bielkina-Kovalchuk, Olena (My University, 2025)
In the context of modern social transformations, innovative administration of social support and interagency cooperation are key to enhancing social service efficiency. Integrated management models using digital technologies, cross-sectoral coordination, and organizational partnerships ensure systematic, coherent support. This study examines the theoretical and methodological foundations of interagency cooperation as a tool for optimizing resources, strengthening social cohesion, and improving community-level social policy. A survey of 876 service recipients and 188 providers revealed high awareness of integrated approaches (59.7% recipients, 75% providers) and positive impacts on vulnerable groups (82.5% recipients, 88.8% providers). However, full implementation of innovative practices remains limited, with barriers including regulatory gaps, a lack of unified methodology, and insufficient professional training, highlighting the need to enhance human, regulatory, and digital support.
Keywords: social services; community; counseling; interagency cooperation; social support; social policy